Use of antidepressants in patients with depression and comorbid diabetes mellitus: a systematic review - Roopan, Subethini; Larsen, Erik Roj (Acta neuropsychiatrica, 2017)
Depression may be difficult to treat and with comorbid diabetes mellitus (DM) it is an even bigger challenge. This article aims to evaluate antidepressants most suitable for patients with depression and comorbid DM. Design and methods Initially we searched for randomised, controlled double-blind trials of treatment with antidepressants in depressed with DM but there were only a few studies and many of them were small trials. Thus, we decided to include studies that were not only randomised-controlled trials. In total, we ended up with 18 articles for our purposes. The combination of depression and DM may be harmful as depression has a strong impact on psychosocial and medical outcomes in patients with DM. Almost all of the trials in this review showed a reduction in depressive symptoms after treatment with an antidepressant in the acute as well as during maintenance phase. It showed that depression improvement had a favourable effect on glycaemic control that was weight independent. Some studies included only subjects with minor depression or with suboptimal-controlled diabetes making it difficult to show an effect. From these data, we will recommend choosing an selective serotonin reuptake inhibitor (SSRI) if possible to treat a depression among patients with diabetes. If treatment with a tricyclic antidepressant is needed, closer glycaemic monitoring is recommended. Bear in mind that there is a possible risk of hypoglycemia when using SSRIs. Agomelatine and bupropion have shown promising results, but need to be investigated in more trials.